1979
DOI: 10.1002/pssb.2220920228
|View full text |Cite
|
Sign up to set email alerts
|

Isomer shift of Eu2+ in fluorites

Abstract: Mossbauer studies are carried out for divalent europium as dopant in the fluorites CaF,, SrF,, and BaF,. The lslEu Mossbauer isomer shift in these materials increases, increases and decreases, respectively, as the Eu2+ concentration decreases below a few mole percent. Previous explanations of these effects as due to lattice pressure or host covalency are found t o be wrong. Instead these trends are interpreted as primarily due to variations in the admixture of t,he prevalent defect structure of E U~+ O : -F~-~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…10,11,13,14 This can be unambiguously attributed to the fact that the resolved paramagnetic hyperfine splitting, observable even at room temperature (as demonstrated in the present study), has not been recognized in the earlier studies and therefore not considered in the analysis of the spectra. The present study solves a longstanding puzzle in 151 Eu Mössbauer spectroscopy.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…10,11,13,14 This can be unambiguously attributed to the fact that the resolved paramagnetic hyperfine splitting, observable even at room temperature (as demonstrated in the present study), has not been recognized in the earlier studies and therefore not considered in the analysis of the spectra. The present study solves a longstanding puzzle in 151 Eu Mössbauer spectroscopy.…”
Section: Discussionsupporting
confidence: 50%
“…Nitsche et al 12 found a very unusual temperature dependence of the Eu 2+ isomer shift in CaF 2 :1%Eu. Lambe and Schroeer 13 and Schroeer et al 14 extended the Mössbauer studies to lower concentration (0.1% to 10%) and observed an even stronger anomalous variation of the isomer shift with Eu 2+ concentration from 11.3 mm/s (0.1%) to approximately 13.4 mm/s (1%-10%). In addition, these authors reported on a very broad linewidth (up to ≈8 mm/s compared to a common experimental line-width of ≈2.5 mm/s) of the Eu 2+ absorption lines, which they attributed to spin-spin relaxation effects of paramagnetic splitting (known from the above EPR and ENDOR studies).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations